The effect of green banking product and green corporate image on green customer loyality mediated by green customers satisfaction in Syariah banking - Solekah, Nihayatu Aslamatis (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
Banking has a high potential as a role model for other industries in applying the principles of Sustainable Development. Islamic banking is a bank that has a potential bank business model by implementing green banking, as well as provisions of Bank Indonesia as the Central Bank which has included Green Banking as a concept to be implemented in its business practices. This study developed a research framework to explore the relationship between green banking products and green corporate image green customer satisfaction, and green customer loyalty for Syariah Banking. Analysis technique used to analyze the data analysis Path (Path analysis). The results showed that for green banking products and green corporate image effect directly on green customer satisfaction but green banking product has not affect directly toÂ customers satisfaction, opposite green corporate image that affect directly to green customers loyality